The effect of prior exercise intensity on oxygen uptake kinetics during high-intensity running exercise in trained subjects - Nascimento, Paulo Cesar do; Lucas, Ricardo Dantas de; Souza, Kristopher Mendes de; Aguiar, Rafael Alves de; Denadai, Benedito Sergio [UNESP]; Antonacci Guglielmo, Luiz Guilherme (Springer, 2015)
The aim of this study was to compare the effects of two different kinds of prior exercise protocols [continuous exercise (CE) versus intermittent repeated sprint (IRS)] on oxygen uptake (VO2) kinetics parameters during high-intensity running.Thirteen male amateur futsal players (age 22.8 +/- A 6.1 years; mass 76.0 +/- A 10.2 kg; height 178.7 +/- A 6.6 cm; VO2max 58.1 +/- A 4.5 mL kg(-1) min(-1)) performed a maximal incremental running test for the determination of the gas exchange threshold (GET) and maximal VO2 (VO2max). On two different days, the subjects completed a 6-min bout of high-intensity running (50 % a dagger) on a treadmill that was 6-min after (1) an identical bout of high-intensity exercise (from control to CE), and (2) a protocol of IRS (6 x 40 m).We found significant differences between CE and IRS for the blood lactate concentration ([La]; 6.1 versus 10.7 mmol L-1, respectively), VO2 baseline (0.74 versus 0.93 L min(-1), respectively) and the heart rate (HR; 102 versus 124 bpm, respectively) before the onset of high-intensity exercise. However, both prior CE and prior IRS significantly increased the absolute primary VO2 amplitude (3.77 and 3.79 L min(-1), respectively, versus control 3.54 L min(-1)), reduced the amplitude of the VO2 slow component (0.26 and 0.21 L min(-1), respectively, versus control 0.50 L min(-1)), and decreased the mean response time (MRT; 28.9 and 28.0 s, respectively, versus control 36.9 s) during subsequent bouts.This study showed that different protocols and intensities of prior exercise trigger similar effects on VO2 kinetics during high-intensity running.
Keywords: Priming exercise; Oxygen uptake kinetics; Blood lactate; High-intensity running